John Dewey and the art of teaching toward reflective and imaginative practice - Simpson, Douglas J.; Aycock, Judy C.; Jackson, Michael J. B. (Michael John Brierley) 1943- (SAGE, 2005)
'John Dewey and the Art of Teaching' is an engaging and accessible introduction to the art of teaching as seen through the eyes of John Dewey.